The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.lithos.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

New U-Pb SHRIMP-II zircon intrusion ages of the Cana Brava and Barro Alto layered complexes, central Brazil: constraints on the genesis and evolution of the Tonian Goias Stratiform Complex

Abstract: The Cana Brava, Niquelândia and Barro Alto complexes (Goiás, central Brazil) are three of the largest mafic-ultramafic layered complexes in the world and their origin has been a matter of debate for several decades. One hypothesis suggests that Niquelândia and Barro Alto were both formed by two distinct igneous events at 1.3 Ga and at 790Ma and were later overlapped during tectonic exhumation at 650 Ma; according to this reconstruction Cana Brava belongs to the youngest intrusion at 790 Ma. A second hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
(150 reference statements)
1
12
0
Order By: Relevance
“…The Tonian Goiás Stratiform Complex is located in the northeastern sector of the Goiás State and is considered one of the biggest mafic to ultramafic complexes worldwide. The emplacement of the Tonian Goiás Stratiform Complex is believed to be Mesoproterozoic to Neoproterozoic in age (800-770 Ma; Pimentel et al, 2000;Giovanardi et al, 2017), although its geodynamic setting is still a matter of debate. Many authors (e.g., Pimentel et al, 2004Pimentel et al, , 2006Giovanardi et al, 2017) suggested that continental rift and back-arc extension in continental crust settings are the most appropriate geodynamic scenarios for the Tonian Goiás Stratiform Complex emplacement.…”
Section: Regional Geologymentioning
confidence: 99%
“…The Tonian Goiás Stratiform Complex is located in the northeastern sector of the Goiás State and is considered one of the biggest mafic to ultramafic complexes worldwide. The emplacement of the Tonian Goiás Stratiform Complex is believed to be Mesoproterozoic to Neoproterozoic in age (800-770 Ma; Pimentel et al, 2000;Giovanardi et al, 2017), although its geodynamic setting is still a matter of debate. Many authors (e.g., Pimentel et al, 2004Pimentel et al, , 2006Giovanardi et al, 2017) suggested that continental rift and back-arc extension in continental crust settings are the most appropriate geodynamic scenarios for the Tonian Goiás Stratiform Complex emplacement.…”
Section: Regional Geologymentioning
confidence: 99%
“…4 samples from Cana Brava, 3 from Barro Alto and 3 from Niquelândia were selected for analyses in zircons of the Lu-Hf and U-Pb isotope systematics. Some of these samples were already investigated for U-Pb analysis (Correia et al, 2007(Correia et al, , 2012Giovanardi et al, 2015Giovanardi et al, , 2017b. When possible, Lu-Hf analyses were carried out onto the same crystals and domains analyzed for U-Pb.…”
Section: Samplesmentioning
confidence: 99%
“…2). U-Pb SHRIMP ages from the three samples were discussed in Giovanardi et al (2017b). Samples CB1175 and CB1382 are hydrous granoblastic gabbros with foliation parallel to the complex direction derived by the alignment of pyroxenes and plagioclases.…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations